Exploring the Impact of Front-Line Employees' Extra Role Behavior on Student Loyalty and Retention in a Semi-Government University in the UAE - Aisha Bukhatir Alshamsi; Mohammad Ahmad Al-Hawari; Semiyu Adejare Aderibigbe; Maher Omar; Emran Alotaibi (MDPI AG, 2023)
This study aims to investigate the relationship between front-line employees' (FLEs) extra-role behavior (ERB) and its influence on student satisfaction (SS), student loyalty (SL), and university image (UI), while also examining the moderating effect of student cynicism (SC). Drawing on the service profit chain model, this research proposes a positive relationship between ERB and SS, SL, and UI, with SC acting as a moderator for the relationship between ERB and SS. Using a survey research design, the study was conducted at a semi-government university in the United Arab Emirates (UAE) during a service encounter between FLEs and students, involving 251 students as respondents. Structural Equation Modeling (SEM) was used to analyze the data collected. The findings demonstrated a significant positive relationship between FLE ERB and SS, SL, and UI. Additionally, the study revealed that SC moderates the relationship between FLE ERB and SS, suggesting that highly cynical students are less responsive to employee extra-role behavior. These findings have significant implications for university management and policymakers. By understanding the impact of FLE ERB on student outcomes and the moderating effect of SC, universities can develop and strengthen targeted strategies to enhance SS, SL, and UI.